Pancasila as the Basis for Legal Development in Indonesia - Sajid, Daffa Alim (Universitas Negeri Semarang, 2018)
As determined by the formation of the state that the primary goal is the formulation of Pancasila as the foundation of the Republic Indonesia. Therefore, the principal function Pancasila as the state is based on MPRS No.XX/MPRS/1966 (MPR No.V/MPR/1973 jo, jo No.IX/MPR/1978 MPR), which explained that Pancasila as the source from all source or sources of law rule of law in Indonesia, which is essentially a way of life, consciousness and ideals of the legal and moral ideals which include mystic atmosphere and character of Indonesian nation. And then about Pancasila as the source of all sources of law are explained again in MPR No.III/MPR/2000 about the source of law and order legislation in Article 1 paragraph (3) which states that